2006
DOI: 10.1021/tx060093j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Genomic Biomarkers of Hepatotoxicity Caused by Reactive Metabolites of N-Methylformamide:  Application of Stable Isotope Labeled Compounds in Toxicogenomic Studies

Abstract: The inability to predict if a metabolically bioactivated compound will cause toxicity in later stages of drug development or post-marketing is of serious concern. One approach for improving the predictive success of compound toxicity has been to compare the gene expression profile in preclinical models dosed with novel compounds to a gene expression database generated from compounds with known toxicity. While this guilt-by-association approach can be useful, it is often difficult to elucidate gene expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
19
0
4
Order By: Relevance
“…Comparison of copper-induced mRNA changes with published mRNA profiles of liver responses to various stresses (32)(33)(34)(35) illustrates that the overall pattern of changes in response to copper accumulation (i.e. the combination of most altered pathways) is distinct.…”
Section: Discussionmentioning
confidence: 96%
“…Comparison of copper-induced mRNA changes with published mRNA profiles of liver responses to various stresses (32)(33)(34)(35) illustrates that the overall pattern of changes in response to copper accumulation (i.e. the combination of most altered pathways) is distinct.…”
Section: Discussionmentioning
confidence: 96%
“…Although there have been various reports describing strategies to extract marker genes from the transcriptome data (Hibbs et al, 2004;Mutlib et al, 2006;Tan et al, 2006), the best way has not been established. In the present study, we have started to identify candidates of potential biomarker genes for interpretation of the fundamental mechanism(s) of plasma TG decrease, since our database contains several drugs that cause plasma TG decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Isocyanates are known to be highly reactive (Lee, 1992(Lee, , 1996, and toxicity has been observed with some isocyanates, such as methyl isocyanate, which causes severe pulmonary toxicity (Nemery et al, 1985), and naphthyl isocyanate, which has been shown to be mutagenic (Tamura et al, 1990). Other drugs and compounds that are metabolized to form isocyanates include tolbutamide (Guan et al, 1999), N-methylformamide (NMF) (Mutlib et al, 2006), and anticancer agents, such as nitrosoureas (Rice et al, 2005) and diarylsulfonylureas (Jochheim et al, 2002). Arguments have been made for the role of isocyanates in some of the biologic effects of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Arguments have been made for the role of isocyanates in some of the biologic effects of these compounds. Methyl isocyanate formed from NMF is thought to be dmd.aspetjournals.org related to the hepatotoxicity induced by NMF (Mutlib et al, 2006). Alkyl isocyanates produced by the oxidative metabolism of tolbutamide and N,N9-bis(2-chloroethyl)-N-nitrosourea (BCNU) are known to inhibit glutathione reductase (Guan et al, 1999;Rice et al, 2005).…”
Section: Discussionmentioning
confidence: 99%